PERBEDAAN PRESTASI BELAJAR MAHASISWA BERDASARKAN JALUR SELEKSI MASUK JURUSAN PENDIDIKAN FISIKA UNIVERSITAS SYIAH KUALA - Yenni Claudya; Ngadimin Ngadimin; Melvina Melvina (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2017)
This study aims to determine the differences in learning achievement based on the selection path to the Department of FKIP Physics Unsyiah. This research is a quantitative research. Research population as well as a research sample are all students of physics majors FKIP Unsyiah generation 2013, 2014, 2015, and 2016 are still active as many as 187 people. Technique of data retrieval is done by using documentation technique that is in the form of student's GPA data and data of student admission path for class of year 2013, 2014, 2015 and 2016 for academic year 2016/2017. Data were analyzed with inferential statistics using anova test.Result of analysis of research data obtained by mean of student GPA of SNMPTN, SBMPTN and UMB is equal to 3,00, and result of anova test show F count Ftabel. The conclusion of this research is no difference of academic achievement from physics student of SNMPTN, SBMPTN, and UMB.